A mechanically robust and stable estradiol-loaded PHEMA-based hydrogel barrier for intrauterine adhesion treatment. Issue 42 (18th October 2022) - Xie, Xiangyan; Xu, Ruijuan; Ouyang, Hongyan; Tan, Shiqiao; Guo, Chuan; Luo, Xingqi; Xie, Yuanjie; Wu, Di; Dong, Xiangyu; Wu, Jinrong; Wang, Yi; Zhao, Lijuan
Abstract : The mechanically robust estradiol-loaded PHMH -Si hydrogel could not only release estradiol sustainably and locally but also be a mechanically robust and stable barrier in the uterine cavity, which may be a novel and effective treatment for IUAs. Abstract : Estrogen combined with physical barrier therapy may be a prospective method to repair a damaged endometrium and prevent postsurgical re-adhesion in the treatment of intrauterine adhesions (IUAs), but there lacks a suitable scaffold with good biocompatibility, appropriate mechanical properties, and drug-releasing kinetics. Herein, a mechanically robust and stable barrier based on the poly(hydroxyethyl methacrylate) (PHEMA) hydrogel combined with estradiol-loaded mesoporous silica is designed. The network is formed by covalent bonds and noncovalent coordination bonds, which endow the hydrogel with superior mechanical properties to most reported PHEMA-based hydrogels. Meanwhile, the covalent bonds impart excellent stability to the hydrogel, which maintains its structure and mechanical properties in a simulated uterine fluid for 30 days. The excellent mechanical properties and stability are comparable to those of a typical barrier material intrauterine device (IUD), enabling the hydrogel to be retained in the uterus and removed intact like an IUD. In vitro and in vivo experiments show that the hydrogel possesses good biocompatibility similar to pure PHEMA hydrogels. In addition, the hydrogel releases estradiol continuously and stably, and exhibits a good therapeutic effect in promoting the proliferation of endometrial cells and inhibiting the progression of fibrosis. Therefore, the combinational advantages make the present hydrogel very promising in IUA treatment.